PENGAWASAN PENGELOLAAN PASAR TRADISIONAL OLEH DINAS PERDAGANGAN DAN PERINDUSTRIAN KOTA PEKANBARU (STUDI KASUS PASAR SIMPANG BARU PANAM) - Wafiratul Husna; Pivit Septiary Chandra (Fakultas Ilmu Sosial Dan Politik, Universitas Wijayakusuma Purwokerto, 2023)
This research was motivated by the problem of problems in the supervision of waste management so that researchers wanted to see supervision and the factors that influence it. The purpose of this study is to determine the supervision carried out by the Trade and Industry Office of Pekanbaru City in managing the Panam New Simpang Market. The theory used in this study refers to the theory by Manullung. In theory, the discussion of supervision is based on 3 things, namely: 1. Establish standard measuring devices, 2. Improve assessment (Evaluation), 3. Conduct corrective actions (Corekctive action). This research is a Descriptive Qualitative Research and in collecting data Researchers use methods, Observation, Interviews, and Documentation. Data analysis is using Qualitative Descriptive techniques, with stages of data collection, data presentation, data reduction, and drawing conclusions with informants. The results of this study show that the supervision carried out by the Trade and Industry Office in the market sector in the management of the new intersection market panam Supervision has been carried out by the Trade and Industry Office, but is still not optimal, a factor that becomes an obstacle in the work for officers in the field of supervision is the lack of awareness of traders in paying tax levies. Keywords; Supervision ,Traditional Market, Controlling, Waste Management